2012
DOI: 10.12741/ebrasilis.v5i2.215
|View full text |Cite
|
Sign up to set email alerts
|

Deposition, Incubation Period and Hatching of Eggs from Triatoma juazeirensis Costa & Felix and Triatoma sherlocki Papa, Jurberg, Carcavallo, Cerqueira & Barata, (Hemiptera: Reduviidae) under Laboratory Conditions

Abstract: Abstract. Triatoma juazeirensis Costa & Felix andTriatoma sherlocki Papa, Jurberg, Carcavallo, Cerqueira & Barata are members of the Triatoma brasiliensis Neiva, 1911 species complex. Discovered in the state of Bahia, Brazil, collections from both natural and artificial habitats revealed that they can be found infected by Trypanosoma cruzi (Chagas) suggesting a potential to be vectors for Chagas disease. To contribute to the evaluation of this potential, the capacity of each species to proliferate under labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A recent study found support for high reproductive compatibility between T. sherlocki and the remaining members of T. brasiliensis species complex [ 18 ]. What is more, laboratory progeny between the parapatric T. juazeirensis and T. sherlocki were more vigorous in terms of longevity and dispersal capacity [ 17 , 65 ]. However, despite the physical proximity and genetic compatibility of these two species, no hybrids or intermediate forms have yet been collected in the field, such that factors involved in their isolation remain unknown [ 17 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found support for high reproductive compatibility between T. sherlocki and the remaining members of T. brasiliensis species complex [ 18 ]. What is more, laboratory progeny between the parapatric T. juazeirensis and T. sherlocki were more vigorous in terms of longevity and dispersal capacity [ 17 , 65 ]. However, despite the physical proximity and genetic compatibility of these two species, no hybrids or intermediate forms have yet been collected in the field, such that factors involved in their isolation remain unknown [ 17 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the physical proximity and genetic compatibility of these two species, no hybrids or intermediate forms have yet been collected in the field, such that factors involved in their isolation remain unknown [ 17 - 19 ]. Recent experiments under laboratory conditions showed that T. juazeirensis presents higher reproductive potential as regards fecundity and fertility when compared to T. sherlocki [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the complex is formed by six species and two subspecies [23][24][25][26], which can be identified based on taxonomic keys [14,27]. The taxa of this complex show differences regarding its epidemiological importance, based on biological, ecological, and behavioral parameters [17,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%